“Italy System” as a Case of Innovative Economic Diplomacy - R. O. Raynkhardt (Vestnik MGIMO-Universiteta)
The article deals with the description and analysis of functioning of the Italian national system of economic diplomacy.The author provides an insight into the historical and economic background and conditions of its development from the earliest stages to present time focusing on the latest events (from 2010 onwards).He casts light upon the procedures and mechanisms of interaction between the key national economic-diplomatic agents i.e. ministry of foreign affairs, ministry of economic development, export-promotion agency ITA, investment-attraction agency Invitalia, other authorized bodies (in particular, the Coordination Council on the Internationalization of the Italian Economy - CRII), public and private institutes. The article outlines the main principles of the new system of foreign economic policy "Sistema Paese" which is being implemented since 2011. This concept is based upon efficient cooperation ("team play") between the chief institutes of economic diplomacy with a system approach to elaboration and realizing measures aimed at the internationalization of the Italian business. Innovative elements of "Sistema Paese" do not just imply another reorganization of the MFA, but a completely new approach to issues concerning the position of Italy on the world arena. The author looks into concrete mechanisms of economic diplomacy which basically include measures of national export promotion and assistance to Italian companies in the course of new markets penetration, as well as measures on attraction of foreign direct investment inter alia from developing countries. He mentions that subnational regions of Italy, especially Friuli-Venezia Giulia, Veneto and Sicily, tend to be more and more involved into processes of FDI attraction. Another important trend and particular feature of Italy's modern economic diplomacy is the practice of decentralization of financial management within the MFA system through providing the heads of diplomatic representations with specific competences in this area. Finally, a special emphasis is put on the tight link between instruments of "soft power" and economic diplomacy and their institutional usage, which has deep historical roots.